Citizen web archivists: applying web archiving as a pedagogical tool. Issue 4 (2nd October 2021) - Harris, Kayla; Beis, Christina A.; Shreffler, Stephanie
Abstract: Librarians and archivists preserve information on the Internet through web archiving, but undergraduate students may not have considered that information on the Internet is not always permanent. The asynchronous program, Citizen Web Archiving: Preserving Websites for the Common Good, taught students what web archiving is, why it's important, the ethics of collecting information on the Internet, and how they could contribute to the historical record by archiving websites they deemed important via the Internet Archive's Wayback Machine. The results suggest further opportunities for involving undergraduate students with web archiving initiatives at institutions, and using web archiving as a pedagogical tool.